2001
DOI: 10.1248/bpb.24.1049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Renal Failure on the Pharmacodynamics of Cefoselis-Induced Seizures in Rats.

Abstract: Cefoselis (CFSL), a fourth-generation parenteral cephalosporin, has been marketed in Japan since September 1998. In December 1998, warnings of central nervous system (CNS) adverse effects such as seizures and confusional states were added to the labeling of CFSL. In many cases, these adverse effects were observed in patients who were elderly and/or had renal failure. Therefore renal failure is considered as one of the risk factors for neurotoxicity of CFSL. Since CFSL is mainly eliminated by renal excretion, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…A similar observation has been reported for fluoroquinolones, in which their brain concentrations at the onset of their seizure induction decrease as the renal function decreases [2,3]. As for the precise mechanism accounting for the altered sensitivity, it is not fully understood at present, but various studies have been performed to date [4][5][6], and some of them have suggested that the perturbed neural function and/or modified neural signal handling are largely responsible for the alteration, in which a difference in the potencies of the neuromuscular blockers was reported and an increased sympathetic activity in patients with an impaired renal function was demonstrated [7][8][9].…”
Section: Introductionsupporting
confidence: 68%
“…A similar observation has been reported for fluoroquinolones, in which their brain concentrations at the onset of their seizure induction decrease as the renal function decreases [2,3]. As for the precise mechanism accounting for the altered sensitivity, it is not fully understood at present, but various studies have been performed to date [4][5][6], and some of them have suggested that the perturbed neural function and/or modified neural signal handling are largely responsible for the alteration, in which a difference in the potencies of the neuromuscular blockers was reported and an increased sympathetic activity in patients with an impaired renal function was demonstrated [7][8][9].…”
Section: Introductionsupporting
confidence: 68%
“…This increased CNS sensitivity is possibly related to a perturbation in electrolyte homeostasis in the CNS (17). In fact, there are some reports indicating that changes in the sodium concentration of cerebrospinal fluid (CSF) affect the expression of receptors like the angiotensin type 1A receptor, and this consequently influences various enzyme activities and/or the autonomic nervous system (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Increased brain permeability for radiolabelled inulin and sucrose, for instance, had been demonstrated formerly in uremic rats [13]. Such permeability change or generalised dysfunction of the blood-brain barrier was reaffirmed by the observations of increased protein concentration in the cerebrospinal fluid after renal failure [14] and increased cerebrospinal fluid/serum bromide concentration ratio in uraemic humans, in whom the abnormality was reversible after recovery of renal function [15].…”
Section: Central Nervous System Toxicitymentioning
confidence: 85%
“…Simply taking into account drug distribution in blood and/or cerebrospinal fluid compartments would be of little use for risk estimation. Besides, the convulsive threshold after antibiotic administration in the renal failure population is confounded by the presence of endogenous uraemic toxins such as potentially neurotoxic guanidino compounds [14,23]. Conceivably, these factors account for the difficulty in prediction of central nervous system antibiotic neurotoxicity in clinical practice [24].…”
Section: Central Nervous System Toxicitymentioning
confidence: 99%